2018
DOI: 10.1007/s11306-018-1367-3
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines and considerations for the use of system suitability and quality control samples in mass spectrometry assays applied in untargeted clinical metabolomic studies

Abstract: BackgroundQuality assurance (QA) and quality control (QC) are two quality management processes that are integral to the success of metabolomics including their application for the acquisition of high quality data in any high-throughput analytical chemistry laboratory. QA defines all the planned and systematic activities implemented before samples are collected, to provide confidence that a subsequent analytical process will fulfil predetermined requirements for quality. QC can be defined as the operational tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
610
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 639 publications
(618 citation statements)
references
References 47 publications
6
610
0
2
Order By: Relevance
“…Quality assurance (QA) and quality control (QC) are important processes to ensure robust data acquisition and to maintain confidence in analysis results. Their importance gains increasing recognition in the metabolomics community 5,21,22 and they are required for specific applications by governmental institutions such as the European Medicines Agency (EMA) and the U.S. Food and Drug Administration (FDA) who provide specific guidelines 23,24 . Put simply, while QA defines processes planned and performed to fulfill defined quality requirements, QC comprises measures to report whether these quality requirements have been met.…”
Section: Qc Measures and Metaquac Softwarementioning
confidence: 99%
See 1 more Smart Citation
“…Quality assurance (QA) and quality control (QC) are important processes to ensure robust data acquisition and to maintain confidence in analysis results. Their importance gains increasing recognition in the metabolomics community 5,21,22 and they are required for specific applications by governmental institutions such as the European Medicines Agency (EMA) and the U.S. Food and Drug Administration (FDA) who provide specific guidelines 23,24 . Put simply, while QA defines processes planned and performed to fulfill defined quality requirements, QC comprises measures to report whether these quality requirements have been met.…”
Section: Qc Measures and Metaquac Softwarementioning
confidence: 99%
“…While standardized methods such as the Targeted Metabolomics Kits of Biocrates 8 promise consistent, reproducible and comparable measurements, they are not fully resistant to external influences. These include sample to sample concentration differences, sample handling and processing errors, contamination, sample carryover, batch effects, intra-batch drift, edge effects, missing values of unknown origin and instrument condition 5,7,[9][10][11] . Consequently, multiple checks and controls are required to verify data quality, consistency and reproducibility (i.e.…”
mentioning
confidence: 99%
“…Newer data‐oriented efforts such as deep learning methods (rather than machine learning tools) was demonstrated to help successfully discriminate positive estrogen receptor (ER+) and negative estrogen receptor (ER−) in breast cancer types, and they remain promising for future efforts in the field of cancer metabolomics . With newer efforts to revitalize the existing MSI and data harmonization alongside QA and QC measures in untargeted clinical metabolomics, more robust efforts in cancer and tumor tissue sampling, collection, and analysis would be needed to match the analytical and bioinformatics progress in metabolomics.…”
Section: New Approaches and Technologies For Future Directionsmentioning
confidence: 99%
“…The data preprocessing tools, which define the quality of data generated from a specific platform for further interpretation, are of interest to the community as well. Given that QA and QC as well as system suitability are critical for the data generation and reproducibility thereof, an excellent tutorial underlining the best practices has been delineated for the research community . For instance, a recent study that investigated patterns of missing data in an MS‐based metabolomics experiment of serum samples from the German Cooperative Health Research in the region of Augsburg (KORA) S4/F4 cohort ( n = 1750) using 31 imputation methods revealed that k‐nearest neighbors (KNNs) imputation on observations with variable preselection showed robust performance across all evaluation schemes and was computationally more tractable .…”
Section: Tools For Analytical Platformsmentioning
confidence: 99%